Management of Epileptic Patient in Pediatric and Preventive Dentistry - Prangya Elina Singh (Institute of Medico-legal Publications Pvt Ltd, 2020)
Children are the representative of our future society and their proper growth and development must be thechief concern of all. The condition of the oral cavity in special children like a child having Down syndrome,Epilepsy, Cerebral palsy, Autism is mostly connected to their affliction. Due to a load of medical treatment,normally the parents of these special children do not pursue dental treatment. But in the current situation, thecomplete care for the oral cavity of these children has been provided by the dental professionals. Epilepsyin children is the most common and damaging neurological disorder nowadays. This review shows themanagement of the diseases related to the oral cavity of an epileptic patient in various method and approaches.